Visual Perception and the Emergence of Minimal Representation - Arnellos, Argyris; Moreno, Alvaro (Frontiers in Psychology, 2021)
There is a long-lasting quest of demarcating a minimally representational behavior. Based on neurophysiologically-informed behavioral studies, we argue in detail that one of the simplest cases of organismic behavior based on low-resolution spatial vision—the visually-guided obstacle avoidance in the cubozoan medusa Tripedalia cystophora—implies already a minimal form of representation. We further argue that the characteristics and properties of this form of constancy-employing structural representation distinguish it substantially from putative representational states associated with mere sensory indicators, and we reply to some possible objections from the liberal representationalists camp by defending and qualitatively demarcating the minimal nature of our case. Finally, we briefly discuss the implications of our thesis within a naturalistic framework.